Giant cell tumour of bone in os sacrum of a prepubertal girl – Surgical and medical treatment with zoledronate and denosumab - Signe Sparre Beck-Nielsen; Henrik Hasle; Akmal Safwat; Kestutis Valancius; Bente Langdahl; Ebbe Stender Hansen (Bone Reports, 2023)
A giant cell tumour of bone presented in the os sacrum of a prepubertal girl. Surgery with reconstruction was performed, but total resection was impossible. Zoledronate failed to avoid tumour regrowth, and treatment was changed to denosumab, despite not being recommended for use in growing children. Denosumab treatment for 21 months reduced and stabilized tumour size, the girl became pain free with asymptomatic side effects as mild hypocalcemia, hypophosphatemia and sclerosis of newly formed bone.